Globalization and New Trends in Management – Europe Union Security Aspects - Nowakowska -Grunt, Joanna; Maśloch, Piotr (International Journal of Engineering and Technology, 2018)
This article attempts to define what contemporary globalization is and present opportunities and threats this process generates. The purpose of this paper is also to show how dynamically the reality in Europe is changing and how new threats associated with economy, management and other processes.  The globalization processes of the economies worldwide and the dynamic development of trade and international cooperation create new conditions and threats, under which countries and social-political-economic organizations (e.g. EU) must operate.Experience over the last years has shown, that even the strongest supporters of openness to other values and culture, which are new for Europe, have revised their views, surprised by the scale of illegal immigrations and others EU security aspects.